Using Digital Storytelling to Enhance Students’ Speaking Skills - Laely Nuriyah; Nurhaeda Gailea; John Pahamzah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Many students, particularly those who are studying English as a foreign language (EFL), face a considerable difficulty in achieving a high level of speaking proficiency. The objective of this study is to evaluate the impact of digital storytelling on improving English speaking proficiency.This study utilised a pre-test-posttest group design. The study's demographic and sample comprise 80 students from Class XI IPA in the academic year 2023/2024. The researcher utilised the snowball sampling approach to determine the necessary sample size. Before administering the before and post tests, the researcher evaluated the validity and reliability of the instrument using SPSS. This was accomplished by analysing the scores on the corrected item total correlation, which quantifies the relationship between item scores and the overall item score. The pupils were assigned the labels Group A (experimental) and Group B (control). Afterwards, pupils participate in a Pretest to determine any differences among them. The researcher offered digital storytelling to both groups, but only the experimental group utilised it, while the control group did not. The experimental group will be subjected to a treatment that involves the utilisation of digital storytelling. The T test was utilised as the technique for data analysis. The results showed that the calculated T value was 7.313, and the significance value was below 0.05. Thus, it can be inferred that the use of digital storytelling allows students to improve their English speaking skills. This research is important because it can improve the process of acquiring the English language, namely by emphasising the importance of teachers in teaching digital storytelling during English language learning.